1996
DOI: 10.1148/radiology.198.3.8628872
|View full text |Cite
|
Sign up to set email alerts
|

Small (< or = 3-cm) renal masses: detection with CT versus US and pathologic correlation.

Abstract: A substantial proportion of lesions under 1 cm were not detected with either modality. Neither CT nor US was superior in the characterization of lesions 3 cm or less. CT and particularly US screening studies in patients with von Hippel-Lindau disease should be interpreted cautiously because missed or mischaracterized small renal lesions are a frequent problem in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(127 citation statements)
references
References 0 publications
5
113
1
8
Order By: Relevance
“…CT was better in detecting perinephric extension and lymph nodal involvement in renal masses. Our study correlates with the studies of Kostakopoulos et al [29] (1990) and Jamis-Dow et al [39] (1996) which showed better 2179 sensitivity of CT in detection of small lesions of kidney but this sensitivity is directly proportional to the size of lesion.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…CT was better in detecting perinephric extension and lymph nodal involvement in renal masses. Our study correlates with the studies of Kostakopoulos et al [29] (1990) and Jamis-Dow et al [39] (1996) which showed better 2179 sensitivity of CT in detection of small lesions of kidney but this sensitivity is directly proportional to the size of lesion.…”
supporting
confidence: 92%
“…CT modality was found to be more sensitive in detection of small lesions as one lesion missed on USG was detected on CT, which was measuring less than 3 cm (2.6 cm) in size as shown in Table 9. Similarly, the studies by Kostakopouloset al [29] (1990) and Jamis-Dow et al [39] (1996) showed better sensitivity of CT in detection of small lesions of kidney in comparison to USG but a substantial proportion of small lesions were not visualized with either modality. Study of Bowen et al [1] also concluded that CT and MRI imaging are nearly ideal techniques for the detection, diagnosis, staging, and preoperative evaluation of small renal masses.…”
Section: Discussion:-mentioning
confidence: 71%
“…However, like IVU, it has limited sensitivity for small renal masses. 12 It also has a limited sensitivity for diagnosing transitional cell carcinoma.…”
Section: Evaluation Of the Upper And Lower Urinary Tractsmentioning
confidence: 99%
“…However, the use of US seems to be closely related to the size of the lesion, with small lesions being very difficult to diagnose and characterized. 6 Therefore, in SRM the role of CEUS alone is limited. Multiphasic multislice CT has been considered the standard imaging test for characterizing renal masses in the last three decades.…”
Section: Rationale For Renal Biopsy For Small Renal Massesmentioning
confidence: 99%